Isolasi Bakteri Mananolitik dan Karakterisasi Mananasenya - Anja Meryandini; Rizky Anggreandari; Nisa Rachmania (Universitas Atma Jaya Yogyakarta, 2008)
Isolate RA05 has the highest mannanolytic index and mannanase activity which isolated from copra soil waste from Pasaman, West Sumatra. The best growth condition that produces best mannanase activity of isolate RA05 was achieved from 500 ml flask containing 100 ml medium with 100 rpm agitation. Isolate RA05 showed its mannanase activity in medium containing Locust Bean Gum and coconut meal but not in medium containing kolang kaling. This mannanase had the highest activity on medium containing 2% of coconut meal with optimum condition temperatur 800C and pH 2.5. Adding of 5 mM MnCl2 on the crude enzym increased the activity near 300%. Other kation (Ca2+, Zn2+, Cu2+, Mg2+, Fe2+ dan Co2+) did not display great effect on the activity.